Profil épidémio-clinique des dermatoses chez les enfants vus en consultation dermatologique dans le service de dermatologie du centre national d’appui à la lutte contre la maladie à Bamako (Mali) - Fofana, Youssouf (Pan Afr Med J, 2016)
INTRODUCTION: Skin diseases are a major public health problem in developing countries. In common practice, children represent the most affected segment of the population. This study aims to describe the epidemiological and clinical aspects of skin diseases in children aged 0-15 years receiving dermatological consultation in the Department of Dermatology at the National Center for Disease Control in Bamako (Mali). METHODS: We conducted a cross-sectional study in the Department of Dermatology and Venereology at the National Center for Disease Control from 1 January 2009 to 31 December 2009.Out of a total of 16339 patients who had undergone a dermatological consultation 5149 children were included in the study. RESULTS: Dermatitis-frequency in hospital attending children was 31.51%. We enrolled 2838 boys (55,10%) and 2311 girls (44.90%), with a sex-ratio of 1,22. Patient age ranged from 03 days to 15 years with an average age of 8 ± 5.7 years. Infectious dermatoses accounted for 55.10% of all dermatoses, immuno-allergic dermatoses (32.5%), inflammatory dermatoses (11.85%). CONCLUSION: Our study highlights the severity of infectious and immuno-allergic pathologies and the necessity to promote simple preventive measures such as hygiene, buying a clipper for each child.